The history and distribution of nodulating Paraburkholderia, a potential inoculum for Fynbos forage species. (25th March 2021) - Beukes, Chrizelle W.; Venter, Stephanus N.; Steenkamp, Emma T.
Abstract: Legumes in the Fynbos vegetation of the Western Cape of South Africa have emerged as candidates for domestication, particularly for their adaptation to acidic and infertile soils. However, South African rhizobia have been shown to be very diverse and unique, and a detailed understanding of them is essential to success in forage breeding programs that seek to exploit these "new" legumes. Symbionts of legumes in South Africa that belong to traditional rhizobial genera have been shown to have a unique origin for their symbiotic loci in comparison to members sampled from other regions of the world. Some of the legume tribes in the Fynbos have also been shown to associate predominantly with unique species in the Betaproteobacterial genus Paraburkholderia . The rhizobial members of this genus have two main centres of diversity, of which South Africa is one. In this centre, the legume hosts are principally from the Papilionoideae subfamily while hosts from the mimosoid clade (now in the Caesalpinioideae) are abundant in the South American centre. Not only do these rhizobia differ in terms of host, but their symbiotic loci also show separate origins. The dominance and uniqueness of the Paraburkholderia symbionts, in the context of indigenous South African legumes, makes understanding the history and factors that affect the distribution of this genus essential if successful adaptation and effective nodulation of these legumes in Agriculture are to be achieved globally.